2021
DOI: 10.1016/j.envres.2021.111361
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 virus released from larynx might cause a higher exposure dose in indoor environment

Abstract: COVID-19 virus can replicate in the infected individual's larynx independently, which is different from other viruses that replicate in lungs only, e.g. SARS. It might contribute to the fast spread of COVID-19. However, there are few scientific reports about quantitative comparison of COVID-19 exposure dose (inhalation dose and adhesion dose) for the susceptible individual when the viruses were released from the larynx or lungs. In this paper, a typical numerical model was built based on a breathing human mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 53 publications
(58 reference statements)
1
9
0
1
Order By: Relevance
“…Since body shapes could significantly affect the contamination transport 19 with movement, human‐shape models were used in this study. The source person (SP) was a breathing human with real shape and facial details obtained through CT scanning 35 . However, the facial detail of the SP model was rich and might lead to negative volume cells if used for multi‐person movements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since body shapes could significantly affect the contamination transport 19 with movement, human‐shape models were used in this study. The source person (SP) was a breathing human with real shape and facial details obtained through CT scanning 35 . However, the facial detail of the SP model was rich and might lead to negative volume cells if used for multi‐person movements.…”
Section: Methodsmentioning
confidence: 99%
“…The source person (SP) was a breathing human with real shape and facial details obtained through CT scanning. 35 However,…”
Section: Model Scenes and Mesh Generationmentioning
confidence: 99%
“…Our model incorporates the spreading of aerosols from ‘infected’ agents [ 1 , 28 ] and the measurement of exposure accumulated by the agents in the system. The concentration of aerosols c ( r , t ) follows the, diffusion equation where we also have the source term S and sink term c / τ .…”
Section: Methodsmentioning
confidence: 99%
“…Our model incorporates the spreading of aerosols from 'infected' agents [1,28] and the measurement of exposure accumulated by the agents in the system. The concentration of aerosols…”
Section: Present Monte-carlo Modelmentioning
confidence: 99%
“…e study has shown that the transmission of SARS-CoV-2 could be generated through respiratory droplets and small aerosols [1]. is has led to extensive research on infections and infection control in both outdoor and indoor environments [2][3][4][5][6]. A logical solution to minimizing disease transmission was the isolation of the infected patient.…”
Section: Introductionmentioning
confidence: 99%